2005
DOI: 10.1007/bf03327418
|View full text |Cite
|
Sign up to set email alerts
|

Oral candidosis, denture cleanliness and hygiene habits in an elderly population

Abstract: Only 16.7% of dentures worn by the elderly are properly cleaned. Older dentures tended to be dirtier than newer ones. There was a significant correlation between poor denture hygiene and prevalence of Candida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 8 publications
2
36
1
11
Order By: Relevance
“…Through univariate analysis, previous studies have shown that denture plaque, a criterion used for the evaluation of denture cleanliness, was associated with the roughness of denture materials [39], [40], duration of denture use (i.e., age of dentures) [33], [36], [41], cleaning method [41], and overnight denture removal [24]. Our findings are in line with these results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Through univariate analysis, previous studies have shown that denture plaque, a criterion used for the evaluation of denture cleanliness, was associated with the roughness of denture materials [39], [40], duration of denture use (i.e., age of dentures) [33], [36], [41], cleaning method [41], and overnight denture removal [24]. Our findings are in line with these results.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Baran and Nalcaci [24] reported that denture plaque was correlated significantly with subjects’ age, gender, educational level, and smoking status, but not with denture age or cleaning method. Kanli et al [41] found a significant correlation between denture plaque (defined as cleanliness) and the frequency of cleaning, but our analysis did not yield the same results. Similarly, our results differed from those of Visschere et al [17], who reported that denture plaque was correlated significantly with denture position (maxillary or mandibular).…”
Section: Discussioncontrasting
confidence: 80%
“…However, these techniques are more expensive, and are not available in most hospital centers. The molecular diagnosis is based on nucleic acid hybridization and amplification techniques (5,33,36-38). The objective of the genetic systems is to identify yeasts directly in clinical samples without the need to extract nucleic acids – thereby eliminating the culture time and lowering the costs.…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12] However, simple attitudes such as the removal of the denture during the night and its correct hygiene with the daily usage of disinfecting solutions are mentioned in the literature as effective in the prevention and treatment of denture stomatitis. 4,[13][14][15] Thus, many studies have been performed with the objective of evaluating the efficiency of different disinfecting solutions in the control of Candida genus yeasts, searching for a disinfecting solution that would present excellent antimicrobial activity without harming the patient's health or causing alterations in the physical-structural characteristics of dentures. [16][17][18][19][20] Within this context, the objective of the present study was to evaluate the effect of sodium bicarbonate in the adherence of Candida albicans to thermally activated acrylic resin, comparing it to other disinfecting solutions already mentioned and tested in the literature.…”
Section: Introductionmentioning
confidence: 99%